Importance of Philological Studies in Library Collections - Nasirov, Azimidin; Jumanazarov, Umurzak; Yaxshiyev, Ashur; Jumanazarov, Umid; Sultonov, Oybek; Inatov, Murot; Matkarimov, Nizomjon; Matkarimov, Inomjon (Indian Journal of Information Sources and Services, 2025)
The changing place of philological scholarship in the context of library collections is the topic here, as it has become so significant in the digital transformation era. No longer at the heart of the classic humanities, philology has resurfaced as a central cross-disciplinary method for reading texts, handling cultural heritage, and organizing scholarly communication. In drawing upon both historical and contemporary examples, the research explores the convergence of philology with library science, digital humanities, and archiving. The research foregrounds how libraries themselves have evolved from passive stores of printed volumes to sites of active digital curation, textual analysis, and knowledge communication. The discussion touches upon textual criticism, linguistic research, manuscript preservation, and cataloging within the context of prevailing technological shifts. Special focus is directed towards digital repositories, web-based collections, and AI-driven systems that impact accessibility, interpretation, and sustainability of historical material. Through the employ of literature review and critical evaluation, the article illustrates how philology is as relevant today, not just for the study of textual history, but also to inform the course of future library development, people-oriented services, and digital competency. The article ends by suggesting that renewed focus on philological research in research libraries rebuilds the power of the integrity, depth, and breadth of collections and reinforces combined encounter with the record of civilization.